Comprehensive Management of Odontogenic Myxofibroma in the Mandible: A Four-Year Follow-Up Case Report with a Review of Differential Diagnosis and Treatment Approaches - Joanna Wójcik; Liliia Yefanova; Kacper Nijakowski; Katarzyna Bednarek-Rajewska; Krzysztof Osmola; Maciej Okła (Oral, 2025)
Odontogenic myxofibroma (OMF) is a rare, benign, and slow-growing tumour arising from odontogenic ectomesenchyme. Despite its low prevalence, accounting for approximately 0.5% to 17.7% of all odontogenic tumours worldwide and 3.1% in specific regional studies, it poses significant challenges due to its potential for local recurrence if inadequately excised. This case report presents the clinical course, surgical management, and follow-up of a 35-year-old female patient diagnosed with OMF in the mandibular body region. The patient presented with an osteolytic lesion between the first and second mandibular molars, as confirmed through CT imaging, with dimensions of 31 × 22 × 24 mm. Histopathological examination following excisional biopsy under general anaesthesia confirmed the diagnosis of OMF. The surgical procedure involved mandibular segment resection and reconstruction using an iliac crest bone graft stabilised with plates. Subsequent implantation procedures in 2021 restored dental function, and a four-year follow-up demonstrated excellent outcomes, with no signs of recurrence, periimplantitis, or bone graft compromise. This case highlights the importance of comprehensive imaging, histopathological confirmation, and long-term monitoring in managing odontogenic myxofibroma. Early detection and appropriate surgical intervention significantly improve patient outcomes and quality of life.